LITERACY-BASED SMALL BUSINESS DEVELOPMENT IN THE DIGITAL ERA IN MAKASSAR CITY - Anwar; Romansyah Sahabuddin; Abdul Rahman; Deddy Ibrahim Rauf; Muhammad Rijal Alim Rahmat (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of financial literacy, digital literacy, and business innovation on business performance in Makassar City, both directly and indirectly through entrepreneurial orientation. Micro, small, and medium enterprises (MSMEs) in Makassar City are a vital component of the regional economy, so understanding the factors influencing their performance is crucial to ensuring the sustainability and growth of this sector. In this study, financial literacy is defined as the understanding and ability of business actors to manage the financial aspects of their business, such as cash flow, investments, and financial planning. Digital literacy refers to the ability of business actors to utilize digital technology for operations, marketing, and interactions with customers and business partners. Meanwhile, business innovation refers to the creation and implementation of new ideas in products, processes, or business models that can improve business competitiveness and efficiency. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to business actors in Makassar City who had been operating for at least two years and used digital technology in their operations. A sample of 200 business actors operating in various sectors, such as retail, services, and manufacturing, participated in this study. The data analysis technique used was path analysis, which allows for the evaluation of direct and indirect relationships between variables, with entrepreneurial orientation acting as a mediating variable. The results of the study indicate that financial literacy, digital literacy, and business innovation have a positive effect on business performance. Specifically, business owners with high financial and digital literacy and the ability to innovate have better business performance, both in terms of revenue, profit, and competitiveness. Furthermore, entrepreneurial orientation has been shown to mediate the influence of financial literacy, digital literacy, and business innovation on business performance. This indicates that business owners with a high entrepreneurial orientation are more likely to utilize financial and digital literacy and innovate to improve their business performance. This study provides an important contribution to stakeholders, including business owners, the government, and academics, by emphasizing the importance of improving financial literacy, digital literacy, and business innovation to enhance business performance. Furthermore, this study also highlights the importance of entrepreneurial orientation as a factor that can mediate the relationship between these variables and business performance, which can serve as a basis for developing policies that support the strengthening of entrepreneurship in Makassar City.